PENDEKATAN TAFSIR AL-QURAN DAN PERKEMBANGANNYA DALAM SEJARAH - Abdullah Karim (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2015)
In the half second of 20th century, methodology of tafsir had developed very significant. Muhammad Husain al-Dzahabiy from Egypt, when he wrote his manuscript for his inauguration as a professor, al-Tafsr wa al-Mufassirn,in 1946, stated that there were three approaches of commentary of Qurn. They were al-Matsr, al-Maql, andal-Isyriy. Many people of the ulmul-Qurn scholars quoted his discovery then. Next, in 1966, the work ofMuhammad al-Fadhil bin Asyur from Tunisia, entitled al-Tafsir wa Rijaluh, had been publicated. In this work, hestated a little bit different from the previous that there were three approaches of commentary of Qurn; al-Atsariy, al-Nazhariy, and al-Naqdiy. His work have been important reference for the scholars of ulmul-Qurn then. Thiswriting is going to discuss about approaches in the commentary of Qurn as mentioned above.